2017
DOI: 10.1186/s13071-017-2163-z
|View full text |Cite
|
Sign up to set email alerts
|

Wing morphometrics as a tool in species identification of forensically important blow flies of Thailand

Abstract: BackgroundCorrect species identification of blow flies is a crucial step for understanding their biology, which can be used not only for designing fly control programs, but also to determine the minimum time since death. Identification techniques are usually based on morphological and molecular characters. However, the use of classical morphology requires experienced entomologists for correct identification; while molecular techniques rely on a sound laboratory expertise and remain ambiguous for certain taxa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 42 publications
5
63
0
2
Order By: Relevance
“…Wing shape often varies among populations and species and can even be used for taxonomic inference (Sontigun et al, ). However, compared to size, shape differentiation among populations and closely related species is usually weak and often attributed to (stabilizing) natural selection (Gilchrist et al, ; Gilchrist & Partridge, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wing shape often varies among populations and species and can even be used for taxonomic inference (Sontigun et al, ). However, compared to size, shape differentiation among populations and closely related species is usually weak and often attributed to (stabilizing) natural selection (Gilchrist et al, ; Gilchrist & Partridge, ).…”
Section: Discussionmentioning
confidence: 99%
“…Wing shape often varies among populations and species and can even be used for taxonomic inference (Sontigun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has explored a checklist of medically important flies in the central region of Thailand and found that they have dense populations, especially Chrysomya megacephala (Fabricius) and Musca domestica (Linnaeus) . Correct species identification of flies is a crucial step for understanding their biology, which relates to formulating successful control vectors (Sontigun et al 2017). Species identification of flies is quite challenging because many species have similar morphologies that easily cause identification errors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, organs or other body parts necessary for identifying a species or sex are damaged. Recently, the modern technique has been used to successfully identify 12 species of forensically important blowflies (Sontigun et al 2017) and 12 species of flesh flies in Thailand (Sontigun et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of GM is that it is a cheap method which does not require much equipment, is easy to use and is rapid (Rohlf 2002). Currently, both GM methods have been applied to the study of entomology, including mosquito (Chaiphongpachara 2018;, beetle (Lamb et al 2013), blow-fly (Sontigun et al 2017), spider (Fernández and Marugán 2017), pupae of flies (Chaiphongpachara and Laojun 2019), and bee (De Souza et al 2015). Although it is an effective alternative tool, not all organisms can be identified by this technique, so it is necessary to study the feasibility of applying it to each organism (Ruangsittichai et al 2011).…”
Section: Introductionmentioning
confidence: 99%